An Oral History Interview With Leon Gross, PhD. (August 2019) - Eden, Aimee R.
One of the distinguishing and unique features of being an International Board Certified Lactation Consultant is successful completion of the International Board of Lactation Consultant Examiners examination, necessary for initial and ongoing certification. First offered in 1985, the exam content and scoring criteria have been developed using rigorous psychometric principles. While conducting my dissertation research about the professionalization of breastfeeding support (Eden, 2017), I interviewed Leon Gross, PhD, the psychometrician who oversaw the development of the first exam offered in 1985. He continued in this role through 2013. The interview excerpts below are from a taped interview conducted on March 27, 2011 in Rosslyn, Virginia (AE = Aimee Eden; LG = Leon Gross).